The Effect of Ephedrine and Phenylephrine on the Apgar Score of Newborns After Cesarean Section under Spinal Anesthesia: A Comparative Study (Al-Mansour Journal, 2025)
This study aims to compare the effect of ephedrine and phenylephrine on the Apgar score of newborns after cesarean section under spinal anesthesia. A comparative pilot study was conducted on 40 pregnant women selected for elective cesarean section. They were randomly assigned to two groups: one group received ephedrineAnother received phenylephrine when hypotension occurred. Apgar scores were recorded at the first and fifth minutes after birth, and the data were analyzed using the Kolmogorov-Smirnov test to check the normality of the distribution, followed by the Wilcoxon Signed-Rank test to measure statistical differences.The results showed statistically significant differences between the Apgar scores at the first and fifth minutes for both drugs (p
Keywords: Ephedrine,; Phenylephrine; hypotension during cesarean section; Keywords: Ephedrine, Phenylephrine, hypotension during cesarean section, Apgar assessment; , neonates; spinal anesthesia